The prevalence of overweight and obesity: a measurement-based analysis of 6-9-year-old school children from Montenegro - Ivan Vasiljevic; Jovica Petkovic (Frontiers Media S.A., 2023)
IntroductionThis study aimed to conduct a measurement-based analysis of overweight and obesity prevalence among 6-9-year-old children in Montenegro.MethodsThe population of this cross-sectional study included 1993 (1059 boys and 934 girls) primary-school children. The sample of anthropometric variables includes body height, body weight and body mass index, as well as nutrition status that were presented based on BMI standardized categories: underweight, normal weight, overweight, and obesity. The descriptive statistics described the means for each variable, while post hoc tests and ANOVA were applied to explore differences between the proposed means.ResultsThe results indicate the overweight (including obesity) prevalence was 28% (15% of overweight and 13% of obese children), while boys have a higher overweight prevalence rate than girls. In addition, the tendency of higher prevalence rates to differ by age in both sexes is observed. This study also confirmed that overweight and obesity are affected by geographical regions but not by the level of urbanization in Montenegro.DiscussionThe innovation of this study is reflected in the fact that the overweight and obesity prevalence rates among 6-9-year-old children are within an acceptable range in Montenegro, since it does not deviate from the European average, but further interventions and continuous monitoring are necessary, due to the specific nature of this issue.